Stakeholder Engagement in ESG and Its Impact on Financial Reputation in Property - Denpharanto Agung Krisprimandoyo; Lina Mahardiana; Garry Brumadyadisty; Siska Armawati Sufa; Maryam Maryam (CV. AFDIFAL MAJU BERKAH, 2026)
This study analyzes the role of stakeholder engagement in ESG practices in shaping corporate reputation and financial performance within the real estate industry in Southeast Asia. The primary issue lies in the unclear mechanism through which stakeholder engagement generates financial value. This research aims to examine both the direct and indirect effects of stakeholder engagement on financial performance, with corporate reputation serving as a mediating variable. The study adopts a quantitative approach by surveying 150 ESG professionals and analyzing the data using PLS-SEM. The measurement model demonstrates strong reliability and validity, with indicator loadings ranging from 0.742 to 0.896, Composite Reliability values between 0.888 and 0.926, and AVE values between 0.614 and 0.718. Structural results indicate that stakeholder engagement significantly influences corporate reputation (β = 0.704; T = 18.024; R² = 0.496; f² = 0.983), but does not exert a significant direct effect on financial performance (β = 0.126; T = 1.162; f² = 0.013). Corporate reputation significantly affects financial performance (β = 0.539; T = 4.832; R² = 0.402; f² = 0.245). The significant indirect effect (β = 0.379; T = 4.393) confirms full mediation. Q² values of 0.344 and 0.278 confirm predictive relevance. These findings indicate that ESG-related financial benefits arise through reputation rather than through engagement activities alone. Firms should prioritize authentic and credible engagement to build sustainable reputational capital.